Given the expression:
![\ln 3+\ln 9](https://img.qammunity.org/2023/formulas/mathematics/high-school/2nlheiad2a9qmiktdq6eiwfl8owsthdb1c.png)
the given logarithms are written to the base (e), we will change the base to 3
First, we will simplify the expression then change the base to 3
As we know: ln(AB) = ln A + ln B
so, the given expression can be written as:
![\ln 3+\ln 9=\ln (3\cdot9)=\ln 27](https://img.qammunity.org/2023/formulas/mathematics/high-school/whvh8r0kbx110jwf8s4hq5mn9oiekh3aho.png)
now, we will change (ln 27) from the base (e) to the base (3) as follows:
![\begin{gathered} y=\ln 27 \\ e^y=27 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/jj84m8kau5azb3dwb4yu8okve96xw92clu.png)
Now, taking the logarithm to the base 3
so,
![\begin{gathered} \log _3e^y=\log _327 \\ y\cdot\log _3e=\log _33^3 \\ y\cdot\log _3e=3\cdot\log _33 \\ y\cdot\log _3e=3\cdot1 \\ y\cdot\log _3e=3 \\ \\ y=(3)/(\log _3e) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/nhlw288rww8z97l9my2qitk5ebimlp7tvv.png)
so, the answer will be:
![(3)/(\log _3e)](https://img.qammunity.org/2023/formulas/mathematics/high-school/fdgpsnvai6o9htbj3veisz1j8jb3ne3u0j.png)